The Tenderfoot : A Novel - Vaughan, Robert, 1937- (Thorndike, Maine : Center Point Large Print, 2023)
"When Turquoise Ranch hand Curly Stevens goes into Flagstaff to meet a new employee arriving on the train, his first impression of Rob Barringer is how big and strong the tenderfoot is. Robs eagerness to learn and his willingness to take on the most difficult jobs wins everyone over, including ranch foreman Jake Dunford, and Melanie Dunford, his beautiful daughter. Rob is well- educated, and his demeanor and intelligence catch the attention of Melanie, causing him difficulty with ranch manager Les Garrison, who believes he has an exclusive right to Melanie. Garrison makes life difficult for the ranch hands, and Rob in particular. When Jake Dunford makes a public accusation that the ranch manager is stealing from the ranch, Garrison reacts by firing everyone, but it is Garrison who is in for a big surprise."--
Keywords: Ranches -- West (U.S.); Fiction; Man-woman relationships -- Fiction; Frontier and pioneer life -- West (U.S.); Fiction; West (U.S.) -- History -- 19th century; Fiction; Action and adventure fiction; Western fiction; Historical fiction; Large print books